Relationship Between Students’ Social Anxiety and their Self-Esteem at University Level - Khan, Muhammad Asif (International Research Journal of Education and Innovation, 2023)
Social anxiety is a significant problem faced by students in general but at university level. This anxiety negatively affects students’ self-esteem which motivated the scholars to investigate the relationship between students’ social anxiety and their self-esteem. The focus was to investigate the level of students’ social anxiety, their self-esteem level, and the relationship between them. Following null hypotheses, the researchers adopted quantitative correlational research design. Students at Universities in Malakand division of Khyber Pakhtunkhwa constituted the population and through simple random sampling techniques a sample group of 139 students constituted the sample group. The data obtained from the selected respondents through two questionnaires Students Social Anxiety Questionnaire (SSAQ) and Students’ Self-esteem Questionnaire (SSQ). Both these questionnaires were pilot tested to ensure reliability, and its content validity was measured through expert opinions. The collected data was analyzed through descriptive and inferential statistics through SPSS software. The results revealed that average level of social anxiety among students was found, and a high-level of self-esteem was calculated for the students. Furthermore, the results also showed a positive but low correlation between students’ social anxiety and their self-esteem. Based on these results, it was concluded that students are afraid of different social situations including social interactions, making friends and trust on others. Therefore, the researcher recommended the families of all students, to socially interact their children to build their social skills and to the end of their fear and weakness in front of strangers. The researcher mostly recommended to the teacher to involves the students of different curricula, extracurricular activity, and co-Caracalla activities.